Mental health and the COVID-19 pandemic. (1st September 2020) - Gavin, B.; Lyne, J.; McNicholas, F.
Abstract : With the advent of the COVID-19 pandemic, we have witnessed the greatest global challenge in a generation. The full extent of the mental health impact is, as yet, unknown, but is anticipated to be severe and enduring. In this Special Issue dedicated to mental health and the COVID-19 pandemic, we aim to lay the foundation for an improved understanding of how COVID-19 is affecting mental health services both in Ireland and globally. This Special Issue highlights how the mental health effects of COVID-19 stretch to almost every element of society. The issue includes perspectives from several countries across multiple disciplines and healthcare settings. The drive for rapid innovation and service development is clearly evident throughout and provides hope that by working collaboratively we can positively impact population mental health in the months and years ahead.